PG70 Using high fidelity simulation to prepare trainee advanced critical care practitioners for independent practice. (10th November 2020) - Stratton, Emily; Hunter, Sophie; Coleman, Sophie; Evans, Laura; Bailey, Paul
Abstract : Introduction: Advanced Critical Care Practitioners (ACCPs) are a growing part of the interdisciplinary team within intensive care departments. At Nottingham University Hospital NHS Trust, trainee ACCPs participated in a simulation day designed by critical care fellows and the Trent Simulation and Clinical Skills Centre. The pilot aimed to address identified learning needs and improve trainee ACCPs confidence in becoming independent practitioners. Method: The pilot involved four high fidelity simulations with eight trainee ACCPs taking part over two days. Prior to attendance, ACCPs provided specific learning objectives which were used to develop scenarios commonly faced by junior doctors working in intensive care. Each included a strong human factors element. Participants underwent a structured debrief with faculty and their peers after each scenario. Questionnaires were completed before and immediately after the simulation day. A further questionnaire was completed after three months to assess if outcomes were sustained. Questions required a Likert scale or free text response. Results: Five of the eight trainee ACCPs had not taken part in simulation previously. Results comparing pre and post-course questionnaires demonstrated increased confidence across all areas, particularly in improved awareness of human factors and communicating to the multidisciplinary team. The delayed response questionnaire showed increased confidence compared to pre-course levels with most improvements sustained at values from the immediate post-course survey (table 1 ). Free text responses were positive with half of candidates stating greater awareness of their communication skills after three months. Discussion and Conclusion: This pilot course suggests trainee ACCPs benefit greatly from targeted high fidelity simulation despite limited previous exposure. Confidence in clinical knowledge was not sustained at immediate post-course levels after three months, perhaps due to decay of skills or exposure to more challenging cases in practice. The delayed survey coincided with the start of the COVID-19 pandemic which may have had an impact. Further evaluations could review the longevity of the benefits from simulation to guide how regularly to offer future sessions. The benefits realised from this pilot will lead to further provision of high fidelity simulation for trainee ACCPs.